Transient EDTA‐dependent pseudothrombocytopenia and ulcerative colitis recurrence during chemotherapy: A case of misleading platelet count results attributable to a laboratory artifact - Ayako Watanabe; Hirokazu Toshima; Misa Saeki; Takuya Nagata; Tatsuo Koyanagi; Masumi Minamizawa; Yuka Kashiwabara; Koji Kobayashi; Ken Shimada; Kenji Momo (Clinical Case Reports, 2023)
Key Clinical Message EDTA‐dependent pseudothrombocytopenia as well as myelosuppression should be suspected when thrombocytopenia occurs in patients with autoimmune disease during chemotherapy. Abstract A patient with pancreatic cancer and ulcerative colitis developed transient ethylenediaminetetraacetic acid (EDTA)‐dependent pseudothrombocytopenia with exacerbation of ulcerative colitis during chemotherapy. Unfortunately, pseudothrombocytopenia could not be immediately detected because thrombocytopenia was masked by a reasonable time course of adverse events associated with chemotherapy and ulcerative colitis recurrence. When thrombocytopenia occurs during chemotherapy, especially in patients with autoimmune diseases, EDTA‐dependent pseudothrombocytopenia and bone marrow suppression caused by anti‐cancer agents should be suspected.